2020
DOI: 10.1038/s41598-020-69862-7
|View full text |Cite
|
Sign up to set email alerts
|

An in-silico study of cancer cell survival and spatial distribution within a 3D microenvironment

Abstract: 3D cell cultures are in-vitro models representing a significant improvement with respect to traditional monolayers. Their diffusion and applicability, however, are hampered by the complexity of 3D systems, that add new physical variables for experimental analyses. In order to account for these additional features and improve the study of 3D cultures, we here present SALSA (ScAffoLd SimulAtor), a general purpose computational tool that can simulate the behavior of a population of cells cultured in a 3D scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…While a hypoxic core occurring in 3D culturing systems in standard static condition results in a non-uniform cell distribution within the 3D structure and could affect cell viability in inner regions, 13 , 19 , 33 in our system, perfusion also determines a more homogenous distribution of cells, as shown in Fig. 4 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While a hypoxic core occurring in 3D culturing systems in standard static condition results in a non-uniform cell distribution within the 3D structure and could affect cell viability in inner regions, 13 , 19 , 33 in our system, perfusion also determines a more homogenous distribution of cells, as shown in Fig. 4 .…”
Section: Discussionmentioning
confidence: 92%
“…In this respect, culture conditions largely differ from 2D culture, where all the cells have uniform access to oxygen, nutrients and soluble molecules, such as drugs or cytokines. Indeed, multiple studies 13 , 19 , 33 have shown a non-uniform cell distribution and biological behavior within a 3D scaffold, that often suffers impeded diffusion of oxygen and nutrients inside its structure. Perfusion bioreactor systems have been used to improve medium transport within a scaffold that can contribute to reproduce physiological in vivo conditions, as suggested by many examples published by our or other research groups.…”
Section: Introductionmentioning
confidence: 99%
“…Another interest is the compatibility of these in vitro perfusion systems with a computational tool to model cell-cell, cell-surface, and cell-medium interactions in an in silico mathematical model. This in silico study by computational tool is compatible with single-cell population cultures, co-culture model [87], or 3D microenvironment [88]. Indeed, to comprehend and predict such complex cell culture phenomena, and in designing of optimised cell culture conditions, mathematical modelling and numerical simulations are effective strategies [89].…”
Section: In Vitro Perfusion Modelsmentioning
confidence: 95%
“…To model cell population-level behavior in cancer, researchers are increasingly developing innovative cell lines in silico models which can complement in vivo wet-lab experiments, while overcoming wet-lab limitations ( 206 ) ( Figure 2F ). Such models are employed to investigate cell-to-cell interactions as well as evaluate physical features of the synthetic extracellular matrix (ECM) ( 206 ), etc ( 175 , 207 ). Amongst initial attempts at developing in silico cell line models, in 1989, Shackney et al ( 175 ) proposed an in silico cancer cell model to study tumor evolution.…”
Section: Data-driven Integrative Modeling In Cancer Systems Biologymentioning
confidence: 99%